To the question of studying the legal culture of modern societ - Akhmetov, S.A. (Bulletin of the Karaganda University “Law Series”, 2019)
This scientific study is devoted to the analysis of the legal culture of modern society. The main purpose of the article is to study the characteristics of legal culture, as well as ways to increase its level among the population. The analysis of current problems in this area was conducted. The author considers the essence, content, types of legal culture and its features from the standpoint of various scientific approaches. The author pays special attention to the study of the value aspects of legal culture in conditions in the development of a democratic state and the formation of a civil society in our state. In addition, the article presents a variety of inter pretations of legal culture in its relationship with legal awareness and legal education. The scientific work is written on the basis of available scientific studies of domestic and foreign authors on the nature of legal culture, its influence on the formation of the legal system of the state, the development of legal awareness of society and the eradication of legal nihilism. In the conclusions of the article, the author cites the main directions and measures for the formation of legal awareness and raising the legal culture of modern society, and also gives the author's definition of the legal culture of modern society